2018
DOI: 10.1177/2377960818804742
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Diabetic Ketoacidosis Prevention Intervention in Children With Type 1 Diabetes

Abstract: The objective of this study was to evaluate the effectiveness of a brief, office-based educational intervention to increase parent or patient recognition of the early warning signs and symptoms of diabetic ketoacidosis (DKA). Forty-two patients aged > 13 years and 34 parents of children aged 4 13 years were given a pretest questionnaire about their knowledge of signs and symptoms of DKA and sick day management practices. They received a brief refresher course on sick day management specific to their treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…In recent times, the prevelense of DKA has been decreasing which is a preventable acute complication of diabetes mellitus. 10 We found 51.4% admitted children with DKA were boys. Roaeid and Kablan 11 reported male predominance among patinets of DKA while El-Sharief 12 showed that nearly equally proportion boys and girls was found among patients of DKA which is close to what we observed.…”
Section: Discussionmentioning
confidence: 67%
“…In recent times, the prevelense of DKA has been decreasing which is a preventable acute complication of diabetes mellitus. 10 We found 51.4% admitted children with DKA were boys. Roaeid and Kablan 11 reported male predominance among patinets of DKA while El-Sharief 12 showed that nearly equally proportion boys and girls was found among patients of DKA which is close to what we observed.…”
Section: Discussionmentioning
confidence: 67%
“…Of the 43 documents that provided material for patients, 23 included a handout or posters that could be used by patients ( Fig 3 ). 8 , 18 , 22 , 23 , 25 , 31 , 33 , 34 , 35 , 36 , 37 , 42 , 44 , 46 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 Additionally, 9 documents were publicly available on webpages, 29 , 45 , 48 , 58 , 59 , 60 , 61 , 62 , 63 4 documents referred to wallet-sized cards with instructions for use by patients, 21 , 27 , 28 , 64 and 3 referred to telephonic support. Two studies reported on an interactive tool for delivering sick day medication guidance 65 , 66 ; 1 was a website algorithm specific to insulin adjustment for children with diabetes mellitus, and the content of the other was neither described nor publicly accessible.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were identified that included an intervention, which are characterized using the TIDieR checklist 17 in Table 2 . Two studies tested interventions for providing sick day medication guidance within clinical care, 21 , 67 5 studies tested educational interventions to improve patient knowledge, 18 , 23 , 51 , 65 , 68 2 studies evaluated telephonic support for patients, 69 , 70 and 1 study compared the methods of ketone monitoring. 50 the characteristics of usability studies and randomized controlled trials are provided in Item S2 and Table S2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is provided in Figure 1. Vitale et al 22 demonstrated that a brief educational session on sick day management specific to treatment modality (ie, pump vs injection) and the provision of a take-home flow sheet with guidelines for diabetes sick day management resulted in improved knowledge of signs and symptoms of DKA and proper sick day management and less emergency department visits for adolescents.…”
Section: Discussionmentioning
confidence: 99%